Embracing Psychology for Theology: The Role of Developmental Theories in Christian Spiritual Formation - Jatmiko, Bakhoh; Mtukwa, Gift; Kawengian, Sherly Ester Elaine (Sekolah Tinggi Teologi Simpson Ungaran, 2024)
Spiritual formation is a critical component in faith development toward Christlikeness. When the Christians are no longer growing, they are actively dying. Therefore, various efforts need to be made to help Christians grow. However, many spiritual formation efforts are still segregated, fragmented, or isolated from other discourses. This approach tends to focus only on the spiritual dimension and ignores that an individual has complex dimensions that cannot be separated from one another. To realize a more holistic spiritual formation, this article explores some developmental psychological theories to find approaches that might help to nurture the faith of believers holistically. The research method employed for this research is descriptive qualitative. Data collection was done by library research on various developmental theories from various developmentalists. From the results of the investigation, the author found different insights to realize more effective spiritual formation, namely by involving the community as a social context, taking into account every human dimension, giving space to the process, accommodating the nature of spiritual growth as multi-faceted and multi-directional, and presenting various experiences in the process of forming spiritual disciplines.